Upaya Meningkatan Hasil Belajar Kebugaran Jasmani Dengan Menerapkan Model Pembelajaran Kooperatif Tipe Student Teams Achievement Division (STAD) - Ni Ketut Ratih Wulandari; I Gede Agus Adi Saputra; Ni Wayan Ariawati (Nian Tana Sikka : Jurnal ilmiah Mahasiswa, 2024)
This research is classroom action research, this research was conducted in class X6 of SMA Negeri 8 Denpasar. Based on the researcher's initial observations at SMA Negeri 8 Denpasar, several problems were found that affected student learning outcomes, especially physical fitness material. As an alternative to solving existing problems, researchers provide a solution in the form of putting into practice a cooperative learning model of the Student Teams Achievement Division (STAD) type with the aim of improving the physical fitness results of class X6 students. This investigation is classroom action research, this investigation was carried out in class X6 of SMA Negeri 8 Denpasar. A population of 45 people was used, and the entirety was used as a sample. The cycle in this research was carried out until it reached completion in accordance with the KKTP that had been determined at SMA Negeri 8 Denpasar, namely 75. After implementing the STAD type cooperative learning model, the average final score of students increased beyond the KKTP that had been determined. It can be concluded that the application of the STAD type cooperative learning model can improve physical fitness learning outcomes in class X6 students at SMA Negeri 8 Denpasar.